Selling Russia's treasures - Semenova, Natalʹja Jurʹevna; Semenova, Natalʹja Jurʹevna (The M. T. Abraham Center for the Visual Arts Foundation, 2013)
The lessons of the museum sales / Mikhail Piotrovsky -- The temple of fine arts / Amir G. Kabiri -- Inspired by the past / Dmitry Gourji -- Citizens, preserve monuments of art! -- The Romanov treasure trail -- The pillage of the Russian Church -- Russian icons and art market / Yuri Pyatnitsky -- The palace-museums / Rifat Gafifullin -- The destruction of the Hermitage / Elena Solomakha -- Museum of Modern Western Art : bargain sales of the 1920s-1930s / Alexey Petukhov -- Books for sale / Elena Emelianova -- Buyers, collectors and collections -- In place of an epilogue / Pavel Khoroshilov -- The Russian crown jewels / Victor Nikitin -- Russian icons in European collections / Yuri Pyatnitsky